P105 Coping in Inflammatory Bowel Disease: insights from the Crohn's and Colitis UK national survey. (27th May 2021) - Marshall Mr, J; Rowse, G; Hollobone, S; Afhim, S; Oliver, P
Abstract: Background: Inflammatory bowel disease (IBD) is a chronic condition that adversely affects quality of life (QoL) and well-being. Factors associated with coping in IBD include disease activity, the presence of arthropathy and illness perceptions such as personal control. The evidence in this field is, however, limited by small sample sizes. The aim of this study was to use data from a national survey to identify factors associated with coping in a large sample of IBD patients. Identification of factors associated with coping may help inform the development of targeted interventions to improve psychological well-being. Methods: A national postal and online survey was conducted by the charity Crohn's & Colitis UK of its members in 2018. Participants were asked to complete a questionnaire which was co-produced by the charity and University of Sheffield, following focus groups of key stakeholders. The survey collected demographic and disease-related information as well as Likert item responses to questions relating to well-being, including coping. The response rate was 22.2%. To examine factors associated with coping, ordinal regression analysis was performed. Results are presented as adjusted odds ratios (ORs). Results: 8012 respondents were included in the analyses. The mean age of respondents was 45 years (SD =16 years) with 69% being female. The majority of respondents had a diagnosis of Crohn's disease (78%) with 53% of participants self-reporting that they were in remission at the time of the survey. In multivariable analyses, the adjusted odds of females reporting difficulty in coping was 1.6 times higher than that for males (95% CI 1.43–1.79). The odds of those with active disease reporting more difficulty in coping were approximately twice that of those in remission (95% CI 2.38–2.93). Several well-being factors were found to be associated with coping, even after adjusting for personal and disease related characteristics (such as severity of symptoms and disease activity). Participants who had reported less understanding and felt they had less control of their IBD, had higher odds of difficulty in coping with their disease (95% CI 0.76–0.85 & 0.64–0.72 respectively). Participants who experienced disease-related stigma were also more likely to have difficulty in coping (95% CI for 1.99–2.26). Conclusion: In this large survey of IBD patients, coping was associated with gender, disease characteristics and a number of psychological factors, which may be amenable to intervention to improve the QoL and well-being of patients with IBD. Efforts are required to improve public awareness of the impact of IBD in order to reduce stigma. Further research is required to understand these relationships and constructs through the use of validated measures.